210Po and 210Pb distribution, dissolved-particulate exchange rates, and particulate export along the North Atlantic US GEOTRACES GA03 section. (June 2015) - Rigaud, S.; Stewart, G.; Baskaran, M.; Marsan, D.; Church, T.
Abstract: Vertical profiles of 210 Po and 210 Pb in the water column were measured in the dissolved phase (<0.45 µm), and small (0.8–51 µm) and large (>51 µm) particles at seven stations along the US GEOTRACES North Atlantic Zonal Transect (GA03). Mass balance calculations were employed to assess nuclide exchange rates at the dissolved-small particle interface and between small and large particles, and to quantify export with settling large particles. In the surface ocean, 210 Po scavenging is linearly correlated with the concentration of particulate organic carbon (POC) in large particles, supporting the role of biogenic particle in 210 Po bioaccumulation and export. In stations near the coast, this link is more complex due to the variable source of biogenic material and temporal changes in the surface biogeochemical and physical conditions. At depth, 210 Po exhibits significant widespread deficit with respect to 210 Pb that could in part be attributed to in situ 210 Po scavenging and may be related to surface biological productivity. As previously reported the 210 Pb scavenging rates in the surface ocean were higher at ocean margins. At depth, 210 Pb scavenging increases with depth and eastward due to the increase of adsorption sites available in the benthic layers and to a regional contribution of benthic 210 Pb scavenging and/or particle flux, respectively. The benthic nepheloid layer (BNL) and the Hydrothermal TAG plume distinctly enhance 210 Pb scavenging due to increased surface adsorption in association with resuspended or freshly formed particles. In contrast, 210 Po is not seen to be significantly scavenged in these environments due to its relatively short half-life and the long residence time of particles.